Keamanan Kranberi dalam Pencegahan Infeksi Saluran Kemih: Analisis - Judian, Terence (Cermin Dunia Kedokteran, 2025)
Urinary tract infection is a common disease with high recurrence. UTI is usually treated with antibiotics, however high bacteria resistance towards first-line antibiotic treatment is becoming a health issue. Cranberries have been shown to prevent the adhesion of bacteria to host cell, hence preventing UTI. This systematic review aimed to determine the effectivity and safety of cranberry for prevention of urinary tract infection. Systematic Review was done with search engine from Google Scholar, PubMed, and ScienceDirect, starting with forming clinical question using PICO framework. Studies included was selected based on inclusion and exclusion criteria. The outcomes extracted from each study are the effectiveness and safety of cranberries in UTI prevention. Eight studies were reviewed, seven studies concluded that cranberries can significantlyprevent UTI, while 1 study found that the result was not significant. Three studies reported minimal adverse effect in a small percentage of patients. Cranberries can reduce the incidence of recurrent UTI with minimal adverse effect. PACs (proanthocyanidins) in cranberries can prevent bacteria adhesion, therefore preventing colonization of the bacteria in the urinary tract. Further research on dose and duration are required.